Pengaruh Kontaminsi Saliva terhadap Kekuatan Tarik antara Resin Komposit dengan Jaringan Dentin - Andi Soufyan; Decky J. Indrani; M. Erlinda (Faculty of Dentistry, Universitas Indonesia, 2013)
Composite resin are restorative materials having color similar to teeth and have been widely used in dentistry. The successful application of composite resin influences the duration of the restoration in the oral cavity. The aim of this research is to describe the influence of artificial saliva contamination and the application of re-conditioning on tensile bond strength of composite resin to dentin. In the control group, the dentin were etched, bonding were applied and composite resin were restored on the dentin. In the group with artificial saliva contamination without re-conditioning, the dentin were etched, bonding were applied and then contaminated with artificial saliva, dried and then restired with composite resin. While the group with artificial saliva contamination with re-conditioning, the dentin were etched, bonding were applied and contaminated with artificial saliva, and then etched and applied bonding agent and restored composite resin.Bond strength test used "Universal testing machine, AG 5000. The results showed that highest value of tensile bond strength of composite resin to dentin was at the control group. It can be concluded that artificial saliva contamination decreased tensile bond strength while  re-conditioning application increased it. DOI: 10.14693/jdi.v15i2.69dentin